The Sound of Guilt: Psychoanalytic Themes in Edgar Allan Poe's The Tell-Tale Heart - Shamis uddin Larik,; Suhail Ahmed Solangi ,; Faizan Ali, (Dialogue Social Science Review (DSSR), 2025)
The Tell Tale Heart by Edgar Allan Poe is a famous story that looks into the mind of its narrator. It explores feelings of guilt, obsession, and madness. This paper looks at the story using ideas from psychology, especially those created by Sigmund Freud. It talks about basic parts of the mind like the id, ego, and superego, as well as the idea of repression. This paper examines the narrator's heightened anxiety, his obsession with the old man's eye, and the intense guilt that leads him to confess. It shows that Freud’s ideas about the mind help us understand the hidden forces that influence the narrator’s behavior. The paper says that the old man’s heartbeat sounds represent the guilt the narrator has been hiding. This guilt causes the narrator to lose their mental stability. Looking at Poe’s story this way shows that it’s more than just a murder tale. It deeply explores how our minds work and the unavoidable effects of hidden desires and breaking moral rules.